Metodologi Kritik Hadits antara Muhaditsin versus Orientalis - Kuswadi, Edi (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2016)
Islamic scholars have conducted hadith criticism to ascertain whether or not a hadith comes from the Messenger or not. Hadith criticism is not to to judge the wrongness or prove the untruth of the Prophet's words, but simply to test the devices that contain information about the Prophet. SAW, but simply test the devices that contain information about him, including testing the honesty of the informer. him, including testing the honesty of the informer. The goal is to test and critically analyze whether the historical facts of the presence of the hadith can be proven, including the composition of sentences that are exposed can be proven, including the composition of sentences that are exposed in the expression of the matan. in the expression of the matan. Furthermore, hadith criticism moves to the level of testing whether the content of the matan expression can be accepted as historically true. as historically true. This is in contrast to orientalists and those who follow them, which is to criticize the hadith in order to cast doubt on the hadith itself. However, their efforts unsuccessful because the Islamic scholars' methodology of hadith criticism is more established than that of the orientalists. than the orientalists